The Role of America in Crises Management: A Study of India- Pakistan Crises (2001-2019) - Salma Naz (Journal of Political Studies, 2022)
The enduring antagonism between Pakistan and India enlarged by thoughts of threat perception has spawned recurring crises. Because of the presence of misperceptions as well as miscalculations the possibility of an accidental clash between both nuclear powers was high. So, through the crisis management technique possible armed collision is controlled. The primary purpose of the study is to analyze the American mediation in the India-Pakistan crises. The nature of the study is qualitative because qualitative research supports explaining comprehensively and helps interpretive objectives to understand the role of America in the India-Pakistan crises. The case study method is applied for the present study and the selected era is from 2001 to 2019. Being a review study descriptive, exploratory and historical approaches are applied to discover the answers of the research questions. This research would offer a guiding structure for studying third-party mediation in the management of the crisis. Consequently, an analysis of this research will support to discover several potential finding of the American involvement in crisis management to keep strategic stability and peace in the South Asian region. But, there is no assurance that the findings and conclusions of this crisis management case study are applied to other contexts or crises